Small farmers and sustainability: Institutional barriers to investment and innovation in the Malaysian palm oil industry in Sabah - Amran, Ahmed; Susan, Martin; Alison, Rieple (2015)
The Malaysian palm oil industry is well known for the social, environmental and sustainability challenges associated with its rapid growth over the past ten years. Technologies exist to reduce the conflict between national development aims of economic uplift for the rural poor, on the one hand, and ecological conservation, on the other hand, by raising yields and incomes from areas already under cultivation. But the uptake of these technologies has been slow, particularly in the smallholder sector.